Gestión Financiera De La Cámara De Agricultura Ii Zona Y Su Incidencia En La Calidad De Servicio Con Sus Socios - Betancourt Pazmiño, Jimmy Abraham (2018)
This research project focuses on the financial management of the Chamber of Agriculture II Zone and its impact on the quality of service with its partners. In order to carry out this project, it was decided to conduct a descriptive investigation at all levels of international, national, local and institutional financial management, indicating how it can influence the quality of service. A strict investigation was made of the terms and factors that intervene in both variables in such a way that it was useful to show in detail each one of the subjects making a selection of the items related to the research project in order to achieve a better understanding of the information . Research techniques were used to gather the information so that an interview was conducted with the Accountant of the Chamber of Agriculture II, measuring perceptions and opinions, and a survey was applied to the associates of the institution in order to obtain real information. directly from those involved. Once the information is obtained, an analysis of the data is developed in order to determine the impact that the financial management of the institution has on the quality of service with its partners in order to subsequently submit a proposal and the results of the suggested alternative.